DIGITAL IMAGE COMPRESSION USING RUN LENGTH ENCODING METHOD - Kristian Siregar (Sean Institute, 2018)
The application of Run Length Encoding (RLE) algorithm in image compression cannot always reduce the size of the image compression results. Giving a Run sign or the number of pixels that have repeated succession can certainly change the size of the image file to be smaller, but very different from the repetitive image pixels but not sequential or not at all will certainly give a large size change in the file compression Image compression files that use Algorithm RLE in applications that are often used by users in general on computers can read image matrices. Thus RLE has a special ability to reduce image files from the others if there is a composition of the value of repetitive image pixels. And to decompress RLE to digital images is also very simple because the file type .rle has information on the order of matrix values ​​consisting of two parts, the odd order is the pixel value for the image and while the even order is the value of the number of repeaters in the previous odd pixel value.